Examining the Reliability of Childhood Apraxia of Speech (CAS) Diagnostic Markers in the Greek Language: Preliminary Results - Nikitopoulou, Christina D; Vlassopoulos, Maria; Potagas, Constantin; Papageorgiou, Charalabos C. (Advances in Social Sciences Research Journal, 2025)
Childhood apraxia of speech (CAS) is defined as “a neurological pediatric speech sound disorder in which the precision and consistency of movements underlying speech are impaired, in the absence of neuromuscular deficits. The core impairment in planning and/or programming spatiotemporal parameters of movement sequences results in errors in speech sound production and prosody.” [1]. Due to the absence of universal consensus on CAS diagnostic markers, it is significant to gain non-English clinicians’ insight on the subject. This study aims to present information regarding the reliability of three segmental and suprasegmental CAS specific speech characteristics that could be used to distinguish CAS from a Phonological disorder (PD) in the Greek language. Participants included 53 children ranging between 5;0 to 5;11 (years; months) with CAS (CAS, n=6), PD (n=7), CAS + PD (n=13), TD (typically developing, n=27). The Greek Phonetic and Phonological Development tool and specific subtests of the Verbal Motor production Assessment for Children (VMPAC) were administered, collecting data regarding sequencing, prosody and consistency of speech errors, during spontaneous and imitated production. Impaired prosody, speech error inconsistency and performance during sequencing tasks was significantly lower in participants with a CAS diagnosis. These findings demonstrate that the three features incorporated in ASHA’s report [1] can indicate the direction for CAS differential diagnosis in the Greek language. It is suggested that the implementation of a broader set of diagnostic criteria would support a CAS diagnosis more efficiently, assisting in the differentiation of the above-mentioned disorders.